Aldosterone and progesterone-secreting adrenocortical adenocarcinoma in a cat with a concurrent meningioma. Issue 1 (11th January 2016) - Leshinsky, Jana; Beatty, Julia A; Fawcett, Anne; Voss, Katja; Makara, Mariano; Krockenberger, Mark B; Barrs, Vanessa R
Case summary: A 12-year-old, male neutered domestic shorthair cat was referred for investigation of suspected hyperaldosteronism due to persistent hypokalaemia, hindlimb ataxia, weakness of 1 month's duration and a left adrenal mass that was detected on abdominal ultrasound. Neurological examination findings at referral were suggestive of a concurrent left forebrain lesion. Hyperaldosteronism and concurrent hyperprogesteronism were confirmed on endocrine testing. On computed tomography (CT) of the abdomen and thorax there was no evidence of local vascular invasion by the adrenal mass or of metastatic disease. CT and magnetic resonance imaging featured a large, focal rim-enhancing extra-axial left forebrain lesion consistent with a meningioma. Surgical excision of the forebrain mass was followed by adrenalectomy 2 weeks later. The tumours were classified on histopathology as a psammomatous meningioma and an adrenocortical adenocarcinoma, respectively. Immunohistochemical staining of the meningioma confirmed the presence of progesterone receptors. The cat remains well 2 years later. Relevance and novel information: In humans, elevated serum progesterone levels have been associated with rapid growth of meningiomas due to the presence of progesterone receptors on the tumour. This is the first report of a cat with a progesterone and aldosterone-secreting adrenocortical adenocarcinoma and a concurrent meningioma. Clinicians should be aware of the potential effect of elevated progesterone on meningiomas in cats.